Divine ‘Pastness’ and the Creation of Hope The Significance of the Sepultus est… - Lindsay, Mark R. 1971- (2021)
This article explores Karl Barth’s exegesis of the ‘sepultus est…’ from the Apostles’ Creed, as articulated in his 1935 Credo lectures. I argue that Barth accords the sepultus a degree of theological significance that is against the grain, not only of the majority of western interpretations of Jesus’s burial, but also of his own later interpretation of it within his Kirchliche Dogmatik. Specifically, this article argues that in his 1935 lectures, Barth exegetes the sepultus in terms of a divine self-surrender to the ‘pure pastness’ that is the ‘state and fate’ of all humanity. As a consequence, the sepultus can then be used as the pivot to a different, and more hopeful, future.
Keywords: Credo; Jesus Christ; Karl Barth; Burial; Memory